A Portable Wireless ECG Monitor Based on MSP430FG439 - Hongli Yang; Jihong Chai (2011 International Conference on Intelligent Computation and Bio-Medical Instrumentation, 2011)
Through researching the ECG wireless monitoring technology, this paper designs a portable wireless ECG monitor. This system is controlled by MSP430 single chip computer, which amplifies and filters the patient's ECG signals and sends data to central controller with ZigBee wireless transmission module. Central controller displays the ECG signals. It implements the real time acquisition and short distance transmission of ECG data. This system is very portable, low power, real time and intelligent. It can use in home healthcare, community healthcare and sport training.